GE_GERICHTE A/1258/2018 vom 10. Dezember 2018 - GE Cour de justice (2018)
BUT D'INTÉRÊT GÉNÉRAL ; EXONÉRATION FISCALE ; FONDATION(PERSONNE MORALE) ; VENTE D'IMMEUBLE ; CONTRAT D'ENTREPRISE ; SILENCE QUALIFIÉ | LDE.83.al2; LDE.42.al1